The future of Jewish philosophy - Tirosh-Samuelson, Hava, 1950- (Library of Contemporary Jewish Philosophers, 2018)
This anthology of original essays reflects on the future of Jewish philosophy in light of the Library of Contemporary Jewish Philosophers (Brill, 2013-2018). The volume assesses the strengths of Jewish philosophy, explores the place of Jewish philosophy within the Western academy as a critique of and contribution to the discipline of philosophy, and showcases the relevance of Jewish philosophy to contemporary Jewish culture. The volume argues that Jewish philosophy is more vibrant, diverse, and culturally significant than its public image implies. Special attention is paid to the interdisciplinary nature of Jewish philosophy, the institutional settings for generating Jewish philosophy, and the contribution of philosophizing to contemporary Jewish self-understanding.